2015
DOI: 10.1097/md.0000000000001630
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Clasped Thumb That Is Forgetten a Syndrome in Clinical Practice

Abstract: Congenital clasped thumb is a progressive flexion and adduction deformity presenting with heterogeneous congenital anomalies. Although the disease is rare, diagnosis is usually delayed due to natural location of thumb within the palm in first 3 months of life.A 4-year-old girl with congenital clasped thumb deformity due to absence of extensor pollicis brevis tendon whose treatment consisted of extensor indicis proprius (EIP) transfer and z-plasty reconstruction to first web space.The patient was so happy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 13 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…In most cases it is diagnosed after third month of life, due to natural for infants to this age position of thumb within the hand but it can also be diagnosed via radiological imaging or the autopsy. [8,11,13]. It is usually observed as an accompanying syndrome in serious genetic dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases it is diagnosed after third month of life, due to natural for infants to this age position of thumb within the hand but it can also be diagnosed via radiological imaging or the autopsy. [8,11,13]. It is usually observed as an accompanying syndrome in serious genetic dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an option of conservative treatment of splinting followed by manual therapy. Unfortunately, it is considered applicable only in very mild cases and with the youngest of patients -Al Smail in his case report described a five year old girl as too old for conservative treatment -it is also considered ineffective in cases of complete agenesis of EPB [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…Representative conditions that can cause flexion deformity of the pediatric thumb are congenital clasped thumb and trigger thumb. Trigger thumb and clasped thumb are characterized by flexion of the IPJ and MPJ, respectively ( 3 , 4 , 7 9 ). However, newborns hold the thumb in their palm until 3–4 months of age ( 10 ), and it is not easy to differentiate between these two conditions until the appropriate age to check the thumb's function is reached.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in this report was misdiagnosed with a trigger thumb, and after receiving the A1 pulley release, the flexion deformity gradually progressed. We attempted to evaluate the characteristics of the clasped thumb and review the literature ( 3 – 5 , 7 , 11 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serbest et al 26 reported a 4-year-old girl with congenital clasped thumb anomaly as a result of the absence of extensor pollicis brevis tendon with treatment such as extensor indicis proprius (EIP) transfer and z-plasty reconstruction to first web space. The deformity related to the absence of tendon in cases of isolated clasped thumb deformity with treatment attempts such as splinting and physical treatment have not been successful, EIP tendon transfer and reconstruction of contracture in first web space with Z-plasty are a simple and yet effective method to obtain functional improvement.…”
Section: Discussionmentioning
confidence: 99%